Bleed air oil contamination particulate characterization - Roth, Jake (Kansas State University, 2015)
Gas turbine engine oil is contaminating the bleed air of an aircraft with enough frequency and intensity that health concerns are of public interest. While previous work measured micro particles and used only a simulator, this work mainly consists of measurements in the nanoparticle and ultrafine range using both the simulator and two different gas turbine engines. No previous research has been conducted using working jet engines to simulate a bleed air system and characterize the oil particulate contamination. Oil was injected into a bleed air simulator and an Allison 250 CC18 turbine engine in order to observe the particle size distributions resulting from thermal degradation and was measured with three particle sizing counters and an FTIR. The aerosol size distributions are given for various temperature and pressure ranges consistent with the process conditions associated with the bleed air in a commercial aircraft. Particle sizes of approximately 80nm to 100nm were observed at temperatures over 200°C while particles similar to injection distributions and smaller than measureable size were observed at lower power settings. Temperature is thought to be the controlling factor affecting particle size above 200°C while blade shear is likely the dominant factor for lower temperatures. The bleed air simulator produced results similar to the gas turbine engine results at higher temperatures, but did not replicate the size characteristics at lower temperatures. The observed particles are ultrafine and situated in the size range that may impact health safety more than larger particles.
Keywords: Particulates; Bleed Air; Oil Thermal Decomposition; Aerospace Engineering (0538); Environmental Engineering (0775); Mechanical Engineering (0548)